2023
DOI: 10.30738/sosio.v9i1.13427
|View full text |Cite
|
Sign up to set email alerts
|

Kesejahteraan psikologis dalam hubungannya dengan kecemasan dan dukungan sosial

Abstract: Penelitian ini dilatar belakangi oleh adanya indikasi kurangnya kesejahteraan psikologis pada masyarakat. Tujuan dari penelitian ini adalah untuk menguji secara empirik hubungan kecemasan dan dukungan sosial dengan kesejahteraan psikologis pada masyarakat Desa Karang Rejek Kecamatan Wonosari Gunung Kidul Yogyakarta. Metoda pengambilan sampel dilakukan secara accidental sampling. Jumlah sampel 98. Data penelitian dikumpulkan dengan menggunakan Skala: Kesejahteraan Psikologis, Kecemasan  dan Dukungan social. Has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Based on the above statement, it can be concluded that academic ability affects student life satisfaction. Purwaningsih et al, (2023) states that an important concept in student life is the happiness of life while undergoing education. Satisfaction with academic results is one of the elements of happiness in students.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above statement, it can be concluded that academic ability affects student life satisfaction. Purwaningsih et al, (2023) states that an important concept in student life is the happiness of life while undergoing education. Satisfaction with academic results is one of the elements of happiness in students.…”
Section: Introductionmentioning
confidence: 99%